Settlement, communication and exchange around the western Carpathians : international workshop held at the Institute of Archaeology, Jagiellonian University, Kraków, October 27-28, 2012 - Kienlin, Tobias L.,; Valde-Nowak, Paweł,; Korczyńska, M.,; Cappenberg, K.,; Ociepka, J., (Archaeopress Archaeology, 2014)
During the international conference 'Settlement, Communication and Exchange around the Western Carpathians' held in Kraków in October 2012, attention was focused on the complex issues of long-term cultural change in the populations surrounding the Western Carpathians, with the aim of striking a balance between local cultural dynamics, subsistence economy and the alleged importance of far-reaching contacts, and communication and exchange involved in this process. Specialists from Germany, Hungary, Poland, Slovakia and the United States met and discussed for two days their archaeological findings relating to questions of (Trans)Carpathian communication, settlement patterns, and agricultural and technological changes that occurred (mainly) during the Neolithic and Bronze Age.